Pelatihan Pembuatan Instrumen Penilaian Berbasis Media Nearpod - Pathuddin, Pathuddin; Nasir, Rahma; Alfisyahra, Alfisyahra; Mubarik, Mubarik; Fajriani, Fajriani (Panrannuangku Jurnal Pengabdian Masyarakat, 2023)
The purpose of this community service is to help teachers understand the benefits and ways of using media to make it easier to evaluate digitally. By using nearpod, teachers can also help students to learn independently from their respective students' homes. The problems faced by teachers are (1) the assessment is done manually and takes up a lot of the teacher's time; (2) The lack of teacher knowledge of technology-based evaluation media makes teachers' productivity low in developing teaching materials and multimedia-based evaluation tools. The method of implementation of activities is carried out in the form of lectures, demonstrations, discussions, and questions and answers. The service was attended by teachers at SMP Negeri 2 Banawa Selatan, Donggala Regency, Central Sulawesi. The result of community service is that teachers can design learning and evaluate using nearpod. The response of the participants to the implementation of the activity was very good, participants hoped that this kind of activity could be re-organized for the future.